Beneficial Effect of Mildly Pasteurized Whey Protein on Intestinal Integrity and Innate Defense in Preterm and Near-Term Piglets - Navis, Marit (Nutrients, 2020)
Background. The human digestive tract is structurally mature at birth, yet maturation of gut functions such as digestion and mucosal barrier continues for the next 1–2 years. Human milk and infant milk formulas (IMF) seem to impact maturation of these gut functions differently, which is at least partially related to high temperature processing of IMF causing loss of bioactive proteins and formation of advanced glycation end products (AGEs). Both loss of protein bioactivity and formation of AGEs depend on heating temperature and time. The aim of this study was to investigate the impact of mildly pasteurized whey protein concentrate (MP-WPC) compared to extensively heated WPC (EH-WPC) on gut maturation in a piglet model hypersensitive to enteral nutrition. Methods. WPC was obtained by cold filtration and mildly pasteurized (73 °C, 30 s) or extensively heat treated (73 °C, 30 s + 80 °C, 6 min). Preterm (~90% gestation) and near-term piglets (~96% gestation) received enteral nutrition based on MP-WPC or EH-WPC for five days. Macroscopic and histologic lesions in the gastro-intestinal tract were evaluated and intestinal responses were further assessed by RT-qPCR, immunohistochemistry and enzyme activity analysis. Results. A diet based on MP-WPC limited epithelial intestinal damage and improved colonic integrity compared to EH-WPC. MP-WPC dampened colonic IL1-β, IL-8 and TNF-α expression and lowered T-cell influx in both preterm and near-term piglets. Anti-microbial defense as measured by neutrophil influx in the colon was only observed in near-term piglets, correlated with histological damage and was reduced by MP-WPC. Moreover, MP-WPC stimulated iALP activity in the colonic epithelium and increased differentiation into enteroendocrine cells compared to EH-WPC. Conclusions. Compared to extensively heated WPC, a formula based on mildly pasteurized WPC limits gut inflammation and stimulates gut maturation in preterm and near-term piglets and might therefore also be beneficial for preterm and (near) term infants.